Melanoma-related changes in skin microbiome - Mrázek, Jakub; Mekadim, Chahrazed; Kučerová, Petra; Švejstil, Roman; Salmonová, Hana; Vlasáková, Jitka; Tarasová, Renata; Čížková, Jana; Červinková, Monika (Folia microbiologica, 2019)
Melanoma is the least common form of skin tumor, but it is potentially the most dangerous and responsible for the majority of skin cancer deaths. We suggest that the skin microbiome might be changed during the progression of melanoma. The aim of this study is to compare the composition of the skin microbiota between different locations (skin and melanoma) of a MeLiM (Melanoma-bearing Libechov Minipig) pig model (exophytic melanoma). Ninety samples were used for PCR-DGGE analysis with primers specifically targeting the V3 region of the 16S rRNA gene. The profiles were used for cluster analysis by UPGMA and principal coordinate analysis PCoA and also to calculate the diversity index (Simpson index of diversity). By comparing the obtained results, we found that both bacterial composition and diversity were significantly different between the skin and melanoma microbiomes. The abundances of Fusobacterium and Trueperella genera were significantly increased in melanoma samples, suggesting a strong relationship between melanoma development and skin microbiome changes.
Keywords: DNA bakterií; DNA primery; melanom; Sequence Analysis, DNA; mikrobiota; Swine, Miniature; kůže; RNA ribozomální 16S; Microbiota; zvířata; Fusobacterium; RNA, Ribosomal, 16S; Swine; genetická variace; sekvenční analýza DNA; Genetic Variation; DNA, Bacterial; Melanoma; miniaturní prasata; DNA Primers; Bacteria; Animals; Disease Models, Animal; prasata; Skin; modely nemocí na zvířatech